Genetic Variants Were Associated With the Prognosis of Head and Neck Squamous Carcinoma - He, Yingzheng; Ji, Pei; Li, Yuancheng; Wang, Ruixia; Ma, Hongxia; Yuan, Hua (Frontiers in Oncology, 2020)
Background：As the sixth most common cancer of worldwide, head and neck cancers (HNC) are springing from oral cavity, pharynx and larynx and there is no strong biomarker for prognosis. Rates of five years survival with HNC remain relatively low in decades with improvement of treatments. Evidence that single nucleotide polymorphisms (SNPs) play a part in cancer prognosis is growing. Methods：We conducted an exome-wide association study among 261 patients with head and neck squamous cell carcinoma (HNSCC) and then validated in The Cancer Genome Atlas (TCGA) database for survival by using the Cox proportional hazards regression models and Kaplan–Meier analyses. Results：After combining the result of the two stages, 4 SNPs were significantly associated with HNSCC survival (rs16879870 at 6q14.3: adjusted HR=2.02, 95%CI=1.50-2.73, P=3.88×10-6; rs2641256 at 17p13.2: adjusted HR=0.67, 95%CI=0.56-0.80, P=7.51×10-6; rs2761591 at 11p13: adjusted HR=2.07, 95%CI=1.50-2.87, P=1.16×10-5; and rs854936 at 22q11.21: adjusted HR=1.92, 95%CI=1.43-2.57, P=1.27×10-5). Besides, we constructed a receiver operating characteristic (ROC) model to estimate predictive effect of the novel SNPs combined with clinical stage in HNSCC prognosis (AUC=0.715). We also found the genotype of rs16879870 and rs854936 was significantly associated with the expression of gene GJB7 (P=0.013) and RTN4R (P=0.047) in cancer tissues of TCGA, respectively. Conclusion：Our findings suggested that the SNPs (rs16879870, rs2641256, rs2761591, rs854936) might play a crucial role in prognosis of HNSCC.